2016
DOI: 10.1007/s10461-015-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

A Livelihood Intervention to Reduce the Stigma of HIV in Rural Kenya: Longitudinal Qualitative Study

Abstract: The scale-up of effective treatment has partially reduced the stigma attached to HIV, but HIV still remains highly stigmatized throughout sub-Saharan Africa. Most studies of anti-HIV stigma interventions have employed psycho-educational strategies such as information provision, counseling, and testimonials, but these have had varying degrees of success. Theory suggests that livelihood interventions could potentially reduce stigma by weakening the instrumental and symbolic associations between HIV and premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…Our findings support the hypothesis that ART scale-up reduces desires for social distance by improving physical health and reducing HIV-related symptom burden, allowing PLHIV to reintegrate as productive members of society and diminishing the association of HIV with economic incapacity 30,31 and “social death” 53 . That this effect is more evident in high-prevalence countries compared to low-prevalence countries lends support to the contact hypothesis put forth by Allport 32 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings support the hypothesis that ART scale-up reduces desires for social distance by improving physical health and reducing HIV-related symptom burden, allowing PLHIV to reintegrate as productive members of society and diminishing the association of HIV with economic incapacity 30,31 and “social death” 53 . That this effect is more evident in high-prevalence countries compared to low-prevalence countries lends support to the contact hypothesis put forth by Allport 32 .…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, we found evidence for a more substantial decrease over time in social distancing in countries with high HIV prevalence compared to countries with low HIV prevalence, whereas similar increases in anticipated stigma were found in high and low prevalence countries. These findings have important implications for policymakers, as they suggest that ART scale-up alone may be insufficient to effect meaningful improvements in HIV-related stigma, and that further initiatives to counter stigma are likely necessary, such as educational campaigns 21,52 , changes to laws that institutionalize stigma 19 , and livelihood interventions for PLHIV 30,31 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although livelihood programs for PLHIV have been implemented and evaluated with promising effects on food access (Wagner et al 2012; Weiser et al 2015), psychosocial functioning (Tsai et al 2017; Wagner et al 2012), and HIV treatment outcomes (Weiser et al 2015), they remain beyond the reach of many treatment-experienced PLHIV in resource-limited settings. Although there are numerous factors that impede adoption of livelihood programs as a component of HIV care in low-resource settings, one barrier is limited evidence on malleable predictors of adequate access to food among treatment-experienced PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have indicated the PLWHA with higher SES would have better prognosis as they usually possessed more intangible (e.g., social support, access to health care) and tangible resources (e.g., medication, food supplies, housing) compared to their peers who were at lower SES [10–13]. …”
Section: Introductionmentioning
confidence: 99%